2016
DOI: 10.5853/jos.2016.00234
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of and Preventive Therapy for Stroke in Patients with Atrial Fibrillation

Abstract: Atrial fibrillation is a major cardiac cause of stroke, and a pathogenesis involving thrombus formation in patients with atrial fibrillation is well established. A strategy for rhythm control that involves catheter ablation and anticoagulation therapy is evolving. A strategy for rhythm control that restores and maintains sinus rhythm should reduce the risk of ischemic stroke that is associated with atrial fibrillation; however, this is yet to be proven in large-scale randomized controlled trials. This paper re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 83 publications
1
16
0
2
Order By: Relevance
“…Furthermore, several reports have shown that neither CHA 2 DS 2 ‐VASc score nor AF recurrence is a consistent predictor of the occurrence of ES after AF ablation therapy . Our results support this finding which might imply the existence of some other factors contributing to the occurrence of ES, which could not be explained clinically.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, several reports have shown that neither CHA 2 DS 2 ‐VASc score nor AF recurrence is a consistent predictor of the occurrence of ES after AF ablation therapy . Our results support this finding which might imply the existence of some other factors contributing to the occurrence of ES, which could not be explained clinically.…”
Section: Discussionsupporting
confidence: 82%
“…Embolism of cardiac origin causes up to 25% of all ischaemic strokes55, through contractile dysfunction, structural remodelling, cardiopathy and stasis, increasing the risk of thromboembolism. Simultaneously, AF increases risk of large artery atherosclerosis, ventricular systolic dysfunction and in — situ small — vessel occlusion56,57. The prevalence of AF is generally low but increases with age58,59.…”
Section: Discussionmentioning
confidence: 99%
“…Thromboembolic risk is linked to different pathophysiological mechanisms, including hemodynamic dysfunction and modifications of hemostatic parameters. Hemodynamic problems are most often due to modifications of blood flow in the left atrium (with the loss of atrial contraction and atrio-ventricular synchronization), atrial tissue remodeling and inflammation processes [5]. Among hemostatic parameters, platelets are important players.…”
Section: Introductionmentioning
confidence: 99%